Hong Kong Sports Institute Limited (HKSI) (Hong Kong Sports Institute, 2022)
The Hong Kong Sports Institute Limited (HKSI) was established on 1 October 2004. The aim of the HKSI is to provide an environment in which sport talent can be identified, nurtured and developed to pursue excellence in sport. Other than sports facilities, the support given to athletes includes elite coaching and training, sports science, sports medicine, strength and conditioning, athlete affairs and education, applied research and sports information.